PENGARUH PENERAPAN METODE EKSPERIMEN TERHADAP PENGETAHUAN SAINS ANAK USIA 4-5 TAHUN DI KB TAULADAN SYAFITRI KOTA PEKANBARU - Juliana Juliana; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims: 1) To determine the child's knowledge of science before the application of the experimental method. 2) To know the scientific knowledge of the child after adoption of the experimental method. 3) To determine how much influence the experimental method to the scientific knowledge of the child. The benefits of this research there are theoretical and practical. This type of research used in this research is the experimental approach of a study that sought influence of certain variables on other variables in strictly controlled conditions. The research sample is graders B2 consisting of 26 children, consisting of 12 men and 14 women. Collecting data using observation and documentation. Based on the survey results revealed that 1) the ability of science knowledge children aged 4-5 years in KB Tauladan Syafitri Pekanbaru before treatment is given in the form of an experimental method is low. 2) The ability of science knowledge children aged 4-5 years in KB Tauladan Syafitri Pekanbaru City after being given treatment in the form of an experimental method has increased and is high. 3) The experimental method has a significant impact on the ability of science knowledge children aged 4-5 years in KB Tauladan Syafitri Pekanbaru. It can be seen that there are differences related to increase the scientific knowledge of the child before and after treatment. 4) The experimental method has the effect of 27.88% in the ability of science knowledge children aged 4-5 years in KB Tauladan Syafitri Pekanbaru.Keywords: Experimental Methods, Knowledge Science2